A Systematic Review of the Potential Implication of Infectious Agents in Myasthenia Gravis - Leopardi, Victoria; Chang, Yu-Mei; Pham, Andrew; Luo, Jie; Garden, Oliver A. (Frontiers in Neurology, 2021)
Background: Myasthenia gravis (MG) is a debilitating autoimmune disorder of unknown etiology in most patients, in which autoantibodies target and destroy nicotinic acetylcholine receptors (AChRs) at the neuromuscular junctions by complement-mediated lysis and antigenic modulation. Objective: To provide a comprehensive synthesis of the evidence examining infectious agents associated with the onset of MG. Hypothesis: We hypothesized that microbes play a pathogenic role in the initiation of MG. Methods: We searched PubMed and Web of Science for relevant primary research. Papers captured by a search algorithm (n = 415) were manually assessed, yielding a total of 42 publications meeting the inclusion and exclusion criteria. An additional 6 papers were retrieved from the reference list of relevant articles. For each pathogen identified in a paper, an integrated metric of evidence (IME) value, ranging from minus 8 to plus 8, was computed based on the study design, quality of data, confidence of infectious disease diagnosis, likelihood of a causal link between the pathogen and MG, confidence of MG diagnosis, and the number of infected patients. Negative IME values corresponded to studies providing evidence against a role for microbes as etiological triggers in MG. Results: One hundred and sixty-nine myasthenic patients infected with 21 different pathogens were documented. Epstein-Barr virus (median = 4.71), human papillomavirus (median = 4.35), and poliovirus (median = 4.29) demonstrated the highest IME values. The median IME for the dataset was 2.63 (mean = 2.53; range -3.79 to 5.25), suggesting a general lack of evidence for a causal link. Conclusions: There was a notable absence of mechanistic studies designed to answer this question directly. While there is a sizable body of literature documenting concurrence of infectious disease and MG, the question of the pathogenic contribution of microbes to MG remains open.